Discriminant analysis of terrestrial animal fat and oil adulteration in fish oil by infrared spectroscopy - Lingzhi, Xu; Fei, Gao; Zengling, Yang; Lujia, Han; Xian, Liu (International Journal of Agricultural and Biological Engineering, 2016)
In order to improve the effective utilization of animal fats and oils, and then ensure the feeding quality and safety in the field of animal husbandry engineering, the discriminant analysis of different species of terrestrial animal fats and oils in fish oil based on Fourier transform infrared spectroscopy was explored in this study. Twenty-seven different species of animal fat and oil materials including fish oil, lard, chicken oil, tallow and suet were studied. The experimental calibration and validation samples were prepared by adulterating different proportions of terrestrial fat and oil in fish oil. Results show that, it is easy to discriminate different species of raw material of fish oil, lard, chicken oil and ruminant fats based on the infrared spectral characteristics, while the distinction of tallow from suet samples is difficult. For the adulterated samples with percentage range of 1%-60% (w/w), ideal results were obtained to discriminate the terrestrial fat and oil ingredients (lard, chicken oil, tallow and suet) in fish oil, the correct discriminant rates for the independent validation set were all higher than 95%. It was proved by further study that the detection limits for the discriminant analysis of lard, chicken oil, tallow and suet in fish oil were 0.8%, 0.6%, 2% and 3%, respectively. Keywords: infrared spectroscopy, fish oil, animal fat and oil, discriminant analysis, detection limit DOI: 10.3965/j.ijabe.20160903.2239 Citation: Xu L Z, Gao F, Yang Z L, Han L J, Liu X. Discriminant analysis of terrestrial animal fat and oil adulteration in fish oil by infrared spectroscopy. Int J Agric & Biol Eng, 2016; 9(3): 179－185.